The prevalence of anemia decreased in Mexican preschool and school-age children from 1999 to 2006 La prevalencia de anemia disminuyó en niños prescolares y escolares mexicanos entre 1999 y 2006 - Salvador Villalpando; Teresa Shamah-Levy; Armando García-Guerra; Verónica Mundo-Rosas; Clara Domínguez; Fabiola Mejía-Rodríguez (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To compare the distribution of anemia in children, based on information from Mexican National Health and Nutrition Survey 2006 (ENSANUT 2006) and Mexican National Nutrition Survey 1999 (ENN-99), and examine the association of anemia with potentially explanatory variables. MATERIAL AND METHODS: Adjusted prevalence and means as well as associations with potentially explanatory variables were assessed by multiple linear and logistic regression models for complex samples. RESULTS: From 1999 to 2006, the prevalence of anemia decreased 13.8 percentage points (pp) in toddlers and 7.8 pp in children 24-35 months of age; it also decreased 0.7 pp/year in urban and rural populations, 1.8 pp/year in indigenous and 0.61 pp/year in non-indigenous toddlers, 1.5 pp/year in children 5-8 years of age and 0.78 pp/year in children 9-11 years of age. In toddlers served by Oportunidades, Hb was inversely associated with indigenous ethnicity (p=0.1) and they had a lower risk of anemia (OR=0.002). In school-age children, age (OR=0.98), affiliation to Liconsa (OR=0.42) and living in the central region (OR=0.56) were protective factors for anemia. CONCLUSIONS: The national prevalence of anemia in Mexico has decreased in the past seven years, especially in toddlers. Being a beneficiary of Liconsa or Oportunidades was protective for anemia. OBJETIVO: Comparar la distribución de la anemia en niños con base en la información de la Encuesta Nacional de Nutrición 2006 (ENSANUT 2006) y la Encuesta Nacional de Nutrición 1999 (ENN99). Asimismo, examinar la asociación de la anemia con variables potencialmente explicativas. MATERIAL Y MÉTODOS: Se calcularon las prevalencias y las medias ajustadas, así como las asociaciones mediante modelos de regresión múltiple lineal y logística para muestras complejas. RESULTADOS: Entre 1999 y 2006 la anemia disminuyó 13.8 puntos porcentuales (pp) en lactantes de 12-23 meses de edad y 7.8 pp en los de 24-35; 0.7 pp/año en prescolares urbanos y rurales, 1.8 pp/año en indígenas y 0.61 pp/año en no indígenas; 1.5 pp/año en niños de 5-8 años y 0.78 pp/año en los de 9-11 años. En preescolares beneficiarios de Oportunidades la Hb se asoció negativamente con indigenismo (p=0.1) y tuvieron un riesgo menor para anemia (OR=0.002). En niños escolares la edad (OR=0.98), ser beneficiario de Liconsa (OR=0.42) y vivir en la región centro (OR=0.56) resultaron ser factores protectores contra la anemia. CONCLUSIONES: La prevalencia de anemia disminuyó en México durante los pasados siete años, especialmente en lactantes. Ser beneficiario de Oportunidades y de Liconsa fue protector para el riesgo de anemia.